ANALYSIS OF PRODUCTION COST CALCULATIONS USING PROCESS COSTING METHOD IN SULI TOFU FACTORY - Rumanintya Lisaria Putri (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
This research took place at Suli Tofu Factory which aims to (1) to know the method of collecting raw materials, direct labor, and factory overhead cost, (2) to know the factory overhead method of imposition cost in determining the basic price of production, (3) calculation of business profit. Method used in this research is direct and indirect interview, and literature study. Furthermore, the evaluation was done on the research conducted by comparing the data and the theory. The results showed that the Suli Tofu Factory has collected and calculated elements of production cost including raw materials, direct labor, and factory overhead cost in each period. The Suli Tofu plant has collected the cost of raw materials either by multiplying the amount of material used by the raw material base price. The Suli Tofu factory has calculated the cost of labor both by multiplying the amount of labor by the number of working days and the fixed daily wage rates. However, there are still some weaknesses pricing of basic production plant Suli Tofu factory: (1) there is no separation between production costs and the costs of non-production, (2) to the factory overhead costs, Suli Tofu Factory only calculate the actual cost spent in cash. Know Factory counts building cost and depreciation in plant overhead cost, (3) no stock card of raw materials.